2009
DOI: 10.1016/j.biomaterials.2009.03.017
|View full text |Cite
|
Sign up to set email alerts
|

On-line observation of cell growth in a three-dimensional matrix on surface-modified microelectrode arrays

Abstract: Despite many successful applications of microelectrode arrays (MEAs), typical two-dimensional in-vitro cultures do not project the full scale of the cell growth environment in the three-dimensional (3D) in-vivo setting. This study aims to on-line monitor in-vitro cell growth in a 3D matrix on the surface-modified MEAs with a dynamic perfusion culture system. A 3D matrix consisting of poly(ethylene glycol) hydrogel supplemented with poly-D-lysine was subsequently synthesized in-situ on the self-assembled monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…The biointerface was created by immersing APTMS or MPTMS modified NW-MOSFETs in 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS) citrate buffered solution of antibody against prostate-specific antigen (anti-PSA, Ortho-Clinical Diagnostics Johnson & Johnson, 34 kDa). The EDC-NHS was utilized to only activate terminal carboxyl (-COOH) group of antibody [16,20] and maintain exposure of its active site for antigen binding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biointerface was created by immersing APTMS or MPTMS modified NW-MOSFETs in 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS) citrate buffered solution of antibody against prostate-specific antigen (anti-PSA, Ortho-Clinical Diagnostics Johnson & Johnson, 34 kDa). The EDC-NHS was utilized to only activate terminal carboxyl (-COOH) group of antibody [16,20] and maintain exposure of its active site for antigen binding.…”
Section: Methodsmentioning
confidence: 99%
“…Surface modification techniques have been applied to functionalize FETs for the specific detection of ions [4,12], DNA [7,13], proteins [4,8], and viruses [14]. In addition, the surface modification or functionalization introduces functional groups and then creates an interface between the biological system and the electronic device for detection of neuronal signals [15] and observation of cell growth [16]. Organosilane molecules are popular candidates for reacting with hydroxyl-terminated surfaces [17].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5A shows an electrochemical biosensor that incorporates the 3D culture in a synthetic hydrogel on a flat electrode surface. 85 Figure 5B shows the transduction principle and the resulting signals of the 2D and 3D culture-based electrochemical biosensors (Fig. 5B).…”
Section: D Cell Cultures In Cell-based Biosensorsmentioning
confidence: 99%
“…Lin et al used a flat microelectrode array to monitor the impedance change during the growth of NIH 3T3 fibroblasts and cortical neurons in a 3D matrix in a label-free manner. 85 Jeong et al reported a similar design of an electrochemical biosensor using several types of sol-gels (alginate, collagen, Matrigel) to grow A549 lung cancer cells in 3D on flat electrodes. 78 Cellular responses to anticancer drugs were successfully monitored.…”
Section: D Cell Cultures In Cell-based Biosensorsmentioning
confidence: 99%
“…Using a three chamber microfluidic device, it was found that when CAF were cultured adjacent to ACC-M, ACC-M cells invaded neighboring matrix and was reduced when MMP inhibitor was GM 6001 was introduced. Similar studies have proven EIS capable of monitoring growth rate of cells embedded inside of a 3-D matrix [119]. Impedance based sensors integrated within culture chambers could actively sense changes in the density of cells trapped within the matrix allowing for real-time cellular invasion assays, allowing for fully automated real-time monitoring of MCTS invasion.…”
Section: A Fundamental Cellular Studiesmentioning
confidence: 98%